Future Identity Matters: The Essence of Adolescence with Comics - Attic, Dan (The Canadian Art Teacher / Enseigner les arts au Canada, 2023)
In 2020, I piloted an art project involving a comic jam giving secondary students an opportunity to explore and express ideas related to identity. I would like to share this exciting teaching idea by presenting what I’ve learned about this approach and the research supporting the creation of comic book-style art as a means to help teens answer the question, “Who am I?”. What began initially as a student meet and greet through their comic book-style creations, has evolved to a more complex framework where students consider hybrid identities while creating fictional characters using digital collage. In most instances, students have referred to past or present experiences in order to access their ideas related to identity. Recently, I recognized the importance of future thinking in adolescence, and that perhaps, through making comic book-style art and participating in comic jams, secondary students might also be able to consider a future self. In the process of becoming adults, teenagers must also be asking the question, “Who will I be?”.